2020
DOI: 10.3389/fnins.2020.00131
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Exercise and Alzheimer’s Disease: A Narrative Literature Review

Abstract: This narrative review aimed to summarize evidence regarding the responses to exercise among patients with preclinical Alzheimer's disease (AD) and the effectiveness of long-term exercise interventions in improving cognitive function and neuropsychiatric symptoms. We performed a narrative review of existing literature on the effectiveness of long-term exercise interventions in improving cognitive function and neuropsychiatric symptoms in patients with AD. Patients with AD who presented with long-term exercise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 46 publications
2
102
0
1
Order By: Relevance
“…Expression of the high affinity binding PAC1 receptor [1] decreased in the testis of AD animals, similar to the CNS [18]. Physical exercise can be protective against Aβ neurotoxicity [34]. In our study, the expression of PAC1 receptor was nearly normalized in TAD animals.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Expression of the high affinity binding PAC1 receptor [1] decreased in the testis of AD animals, similar to the CNS [18]. Physical exercise can be protective against Aβ neurotoxicity [34]. In our study, the expression of PAC1 receptor was nearly normalized in TAD animals.…”
Section: Discussionsupporting
confidence: 63%
“…Controlled training postponed the manifestation of AD in human patients [33] and it has been demonstrated that continuous physical exercise affects the concentration of Aβ in plasma [33]. Various studies have been published in the last few years about the advantages of physical activity on AD formation [34] but its peripheral effects have not been discussed in detail, although increased locomotion and training in B6C3-Tg(APPswe, PSEN1dE9)85Dbo/J transgenic mice have yielded promising results to slow down AD formation [35,36]. Therefore, physical activity can be a possible intervention with potential systemic effects and positive consequences on different tissue regeneration in AD [35].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that a sedentary lifestyle might lead to an earlier AD onset. Recent studies have observed that exercise interventions were capable of attenuating the symptoms of neurodegeneration experienced by AD patients, with comparable observations in rodent models of AD [ 29 , 30 , 31 , 32 , 33 ]. In addition, Liang et al [ 34 ] have shown that physical activity reduces the levels of AD-associated biomarkers (e.g., Pittsburgh compound-B, tau, phosphorylated tau) in the cerebrospinal fluid of cognitively normal older adults…”
Section: Protective Role Of Exercise In Preventing Mood Disorders and Neurodegenerative Diseasesmentioning
confidence: 76%
“…For example, a recent study showed that individuals with diabetes and the ɛ4 allele demonstrated a faster functional decline than those without diabetes (Thomas et al, 2020). Other confounding factors like smoking (Durazzo et al, 2014), physical activity (Meng et al, 2020), and education levels (Meng and Arcy, 2012) could introduce some bias into our results. This information was not included in the dataset.…”
Section: Discussionmentioning
confidence: 92%